2014
DOI: 10.2500/ajra.2014.28.4006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sublingual Immunotherapy in Children Aged 3–13 Years with Allergic Rhinitis

Abstract: SLIT is effective and well-tolerated in children with allergic rhinitis 3-13 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 34 publications
6
52
3
2
Order By: Relevance
“…The findings of Marogna and colleagues (53) have been confirmed by a recent study which investigated the effects of SLIT on new sensitization in Chinese AR children aged 3-13 years (54). Assessment of the number of positive SPTs before and after treatment demonstrated that the onset of new sensitization was observed in only 3.55% of children treated by SLIT for 12 months compared with a significantly greater number of 27.27% of children treated by standard drug therapy.…”
Section: Prevention Of New Sensitizationsupporting
confidence: 66%
See 3 more Smart Citations
“…The findings of Marogna and colleagues (53) have been confirmed by a recent study which investigated the effects of SLIT on new sensitization in Chinese AR children aged 3-13 years (54). Assessment of the number of positive SPTs before and after treatment demonstrated that the onset of new sensitization was observed in only 3.55% of children treated by SLIT for 12 months compared with a significantly greater number of 27.27% of children treated by standard drug therapy.…”
Section: Prevention Of New Sensitizationsupporting
confidence: 66%
“…The recommended optimal duration of AIT to achieve maximal efficacy with safety for AR in children is presently unclear. However, one recent study in China has demonstrated good tolerance and safety of SLIT in children as young as 3 years old with Der f-induced AR with or without asthma (54). Similarly, another study has reported good tolerance and safety of HDM-SCIT in over 5 years-old children with a history of HDM-induced AR or asthma (47).…”
Section: Special Considerations In Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Much attention has been paid to sublingual immunotherapy (SLIT) in recent years, but SLIT in the pediatric population is an area in need of further evidence. Here Shao et al 9 provide sorely needed data to indicate that even in children as young as 3 years of age, SLIT can be both safe and efficacious.…”
mentioning
confidence: 99%